A quantitative risk assessment model for Staphylococcus aureus and Salmonella associated with consumption of informally marketed milk products in Tigray, Ethiopia. Issue 2 (18th December 2019) - Weldeabezgi, Lijalem T.; Atsbha, Teklebrhan W.; Kassegn, Hagos H.; Gebremichael, Teklehaimanot F.; Berhe, Mihret H.
Abstract: The aim of this work was to collect relevant input data for integration into Monte‐Carlo simulation using 10, 000 iterations to obtain quantitative estimates of exposure and associated risk to Staphylococcus aureus and Salmonella . Higher prevalence rates of S. aureus (54.9 vs. 28.3%) and Salmonella (12.9 vs. 11.1%) were observed for raw milk distributed via collection milk collection centers (MCC) compared to those via dairy farms (DF). Prevalence found for S. aureus in traditionally fermented milk averaged only 3.7%. Although the 90% CI estimated probabilities of exposures to S. aureus due to DF and MCC raw milk consumption at levels higher than the D‐R value found were 10.6 and 23.5%, respectively, exposures to Salmonella were within the pathogen's tolerable limit. While annual likely of risk of illness by S. aureus due to DF and MCC raw milk consumptions resulted in up to 24.2 and 48.3% estimated illnesses, respectively, traditionally fermented milk consumption was found very much less risky; and resulted only 2.5% estimated illnesses per‐serving‐per‐year. The corresponding values for Salmonella per‐serving‐per‐year estimated illnesses via raw milk sales are, respectively, 5.72 and 11.41% compared to 1.8 and 4.02% when they come in boiled forms. Abstract :